Rhinoplasty Health Inventory and Nasal Outcomes (RHINO) Scale: Translation, Cross-Cultural Adaptation and Validation for Hebrew-Speaking Patients - Eisenbach, Netanel; Mizrachi, Matti; Dror, Amiel A.; Faris, Rania; Ohayon, Tali Jane; Ronen, Ohad; Sela, Eyal (Facial Plastic Surgery, 2024)
Patient-reported outcomes questionnaires are accepted measurement tools to evaluate procedures results. The Rhinoplasty Health Inventory and Nasal Outcomes (RHINO) scale is an English-language validated and reliable quality-of-life instrument that evaluates both functional and aesthetic outcomes after rhinoplasty, and is not available in Hebrew. We followed the forward-and-back-translation method, defined by the European Organization for Research and Treatment of Cancer. Translation of the RHINO scale and merging it into one version were performed, following back-translation and validation on native Hebrew-speaking patients who underwent rhinoplasty and control healthy group. Lastly, we review and analyzed the results. The translated questionnaire had high reliability measures, demonstrating homogeneity (α value 0.800 in the rhinoplasty group and 0.896 in the control group), test–retest reproducibility with no significant difference (p = 0.5), and high agreement scores represented by the Bland–Altman plot (95% limits of agreement ranged from 8.78 to 9.80). Validity demonstrated by significant differences between the two study groups' mean questionnaire scores (p < 0.001 for rhinoplasty vs. controls, p < 0.001 for preoperative vs. postoperative, and p = 0.002 for postoperative vs. control group) and also between the aesthetic scores and functional scores of the rhinoplasty group before and after the surgery (p < 0.001). There were no reported understanding problems. The Hebrew version of the RHINO scale is a reliable and valid tool for pre- and post-rhinoplasty surgery outcomes measuring among Hebrew-speaking patients, and can improve coordination of expectations, follow-up, and quantify subjective evaluation of the surgery. Level of evidence: IV.
Keywords: rhinoplasty; quality of life; patient satisfaction; patient-reported outcomes; validation; translation